Analisis Penerapan Model Pembelajaran Kooperatif Tipe STAD Dilihat Dari Hasil Belajar IPA - Ni’matur Rohmah; Meirza Nanda Faradita; Ishmatun Naila (Departement of Mathematics Education, 2024)
This study aims to describe the application of the STAD type cooperative learning model to science learning outcomes. This research is a qualitative descriptive study. The subjects of this study were fourth grade students and teachers at MI Muhammadiyah 27 Surabaya. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study show that the application of the STAD Type Cooperative learning model has been carried out properly and well. The STAD Type Cooperative Learning Model has 5 steps, namely the goal of directing learning and motivating students, presenting information, organizing and guiding students in groups, giving quizzes, and giving awards. The impact of applying this learning model can be seen during the learning process, namely by looking at the teachers and students who have implemented the 5 steps of the learning model correctly, so that the learning process goes well. Interaction between students and students with teachers is also visible and students can interact in groups. There was an increase in science learning outcomes after the implementation of the STAD Type Cooperative learning model.